PENERAPAN MODEL PEMBELAJARAN MULTILITERASI DALAM MENINGKATKAN KECERDASAN INTERPERSONAL PADA MATA KULIAH MENULIS KARYA SASTRA BERBANTUAN YOUTUBE - Riana Dwi Lestari (Jurnal Semantik, 2021)
The demands of learning in the 4.0 era require students not only to learn but to interpret learning as a whole, besides that during the pandemic period, learning is done online. The importance of literacy activities among students is not only limited to reading and writing skills but must include two other language skills such as listening skills and speaking skills. To hone these four skills requires continuous activities. Many students are skilled in writing skills but lacking in speaking skills. This can be overcome with a multiliterative learning model that optimizes the four language skills as well as other aspects such as the use of technology and the surrounding environment that can be used as learning materials. After the multiliteration learning stage is achieved, it is expected that students' interpersonal intelligence will change. How they understand other people's situations, how to empathize, work together in groups. This study aims to determine the optimization of the multiliteration learning model in improving interpersonal intelligence in writing literary subjects and to determine the results of multiliterative learning in making short stories. The method used in this research is pre-experimental method. Experimental research using one class with a research sample of 40 students. The results showed that this method was effectively used in improving interpersonal intelligence in writing literary works. The short story writing test results obtained by an average of 63.50 at the pretest while the posttest average was 83.13, so there was an increase of 19.63.